Pengaruh Konsep Diri dan Dukungan Sosial Teman Sebaya terhadap Prokrastinasi Akademik Mahasiswa yang Kuliah Sambil Bekerja dengan Kecemasan Akademik sebagai Variabel Intervening - Setyahandayani, Aimay Adhine; Sugiarti, Rini (Universitas Semarang, 2024)
This study aims to (1) empirically test the effect of self-concept on academic anxiety, (2) empirically test the effect of academic procrastination on self-concept, (3) empirically test the effect of social support on academic challenges, (4) empirically examine the effect of support peer social influence on academic procrastination, (5) empirically testing academic anxiety on academic procrastination, (6) empirically testing the effect of self-concept on academic procrastination as an intervention variable, and (7) empirically testing peer social support on academic procrastination by academic anxiety as an intervention variable. The subjects in the study were 88 students who studied while working and the data collection method used accidental sampling. Research data were collected using four scales, namely (1) academic procrastination scale, (2) academic scale, (3) self-concept scale, and (4) peer social support scale. Data analysis using path analysis using SmartPLS 3.2.9 program. The results showed (1) self-concept has a significant effect on academic anxiety with p = 0.000 where p <0.05, (2) self-concept has a significant effect on academic procrastination with p = 0.000 where p <0.05, (3) social support peers have a significant effect on academic anxiety p = 0.000 where p < 0.05, (4) peer social support has a significant effect on academic procrastination with p = = 0.000 where p < 0.05 (5) academic anxiety has a significant effect on academic procrastination with p = 0.002 where p < 0.05, (6) self-concept affects academic procrastination through academic anxiety p = 0.035 where p <0.05, and (7) peer social support affects academic procrastination through academic academics with p = 0.003 where p < 0.05.